Strategy on Audiovisual Translation of “Enola Holmes” Netflix Movie Subtitle - Violita Violita; Hayatul Cholsy (Universitas Sebelas Maret, 2023)
The article discusses translation strategies of Audiovisual Translation engaged with the movie on Netflix. The research concentrates on translation strategies involved in the AVT subtitle case of an adventure mystery genre in the Netflix movie, Enola Holmes to know the relations. This is an audiovisual translation research in a qualitative descriptive, along with data collecting of English and Indonesian subtitles of Enola Holmes Netflix movie. From the findings, it found nine strategies applied in translating the subtitle of Enola Holmes movie. The domination as the most used strategies is condensation, transfer, and paraphrase, and deletion strategy. The domination strategies produce the final product of subtitles from SL to TL in line with the rules of AVT. Meanwhile, the rest of the least strategies used are expansion, imitation, resignation, decimation, and transcription strategy. The least translation strategies used do not involve much because the strategies contrast with the genre of the movie. Additionally, all of the translation strategies are helpful to produce the efficient subtitles and deliver the original message properly which also does not cross the line of the rules in AVT.